The Red and the Green: The Rise and Fall of Collectivized Agriculture in Marxist Regimes - Frederic L. Pryor (Princeton University Press, 2014)
THE REORGANIZATION of agricultural production units into large-scale state and collective farms has been the most radical change of economic institutions implemented by Marxist governments. In contrast to the nationalization of industry and the replacement of the market by central planning and administration, this institutional change has transformed not only ownership and the way in which production units have functioned, but also the way in which laborers have gone about their work and have related to each other. The forced collectivization of agriculture has also been a searing historical experience in Marxist regimes, during which tens of millions died from starvation and mistreatment, while countless others suffered greatly as a result of the coercion.1 History has not unfolded as nineteenth-century Marxists expected. Socialist revolutions arising from domestic political forces have not occurred first in industrialized nations, but rather, for the most part, in predominantly agricultural countries with relatively low levels of economic development. Furthermore, despite commonplace notions about "peasant conservatism" and the difficulty in reorganizing and reforming agricultural production, Marxist regimes have paid particular attention to transforming the institutions of the rural sector, even while agriculture was the largest sector in the economy and when such changes were most difficult to implement. Furthermore, this institutional change occurred in many countries without extensive agricultural mechanization or high Ievels of rural education and where administration of large-scale agriculture was probably neither cost effective nor necessary. In Marxist terminology, the relations of production were probably too advanced in comparison to the forces of production. Finally, although Marx emphasized the relatively similar paths of development of industry and agriculture and laid great moral stress on the value of all types of physical labor, most of these Marxist governments have organized the two sectors in dissimilar ways and have treated urban and rural workers quite differently, often to the disadvantage of the latter.